Exploring the unintentional impact of human resource management (HRM) policies on gender inequality in the Nigerian workplace (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study delved into the role of human resource management in gender inequality, focusing on policies within the Ibadan Electricity Distribution Company (IBEDC). Examining existing gender-based policies, staff awareness, and perceived effects, the research applied a descriptive design and the Gendered Organisation theory. Thematic analysis of qualitative data from interviews with 27 employees and six management members revealed limited staff awareness of gender policies, with initiatives predominantly benefiting female employees.Recommendations emphasize gender equality programmes for both genders. Future research should scale up andcross-reference participant data with organisational HR policies for a comprehensive understanding.
Keywords: HRM; Gender Inequality; Gender-based Policies; Gendered work